How smart are our companies really? a case study of the current rollout of smart meters in Germany - Knayer, Tobias; Kryvinska, Natalia (Frontiers in Energy Research, 2023)
The digital transformation and the associated challenges for the energy transition and society remain a challenge due to the increasing number of e-charging stations and heat pumps. Nevertheless, the rollout of smart meters selected in Germany affects only a small proportion of the available consumers. Therefore, the aim of this work is to determine the current status of this technology in companies and to answer the question of which factors influence implementation. For this purpose, data from a case study with 386 companies were used. The focus was on the current status of the technology in companies and their knowledge about the technology. The data were recorded during on-site inspections with the help of an energy consultant. In addition, the frequencies of the answers and the implementation of efficiency measures of selected cross-cutting technologies were compared between companies with a smart meter and companies with an analog meter. Our evaluation revealed that 1) 82 percent of companies have a commitment to implementation. 2) Of these, 10 percent have installed a smart meter. 3) Many of the companies were either unaware of the commitment or did not even know what a smart meter was. 4) Companies with a smart meter have implemented more measures in lighting, energy monitoring, energy purchasing and peak load management than companies with an analog meter. To increase implementation and, thus, usage, companies need to be made much more aware. In addition, there is still a lack of value-added services.